Implementation of Religious Literacy in Shaping the Moral Character of Students - Mua, Marianus Muharli; Sawatu, Bernadeth Windy; Rado, Martha Christin (STAI Miftahul Ula Nganjuk, 2024)
The aim of this research encompasses elucidating the implementation of Catholic religious literacy in shaping students' morals, understanding the impact of religious literacy on students' morals, and identifying supporting and inhibiting factors in the application of religious literacy in shaping students' morals. This research utilizes a descriptive qualitative approach. Data is collected through observation, interviews, and documentation, with qualitative data analysis techniques such as data condensation, data presentation, and drawing conclusions. The results of the research indicate that religious literacy activities such as reading and contemplating the Scriptures, Word of God worship, Eucharistic Celebrations, faith catechesis, and others contribute to the formation of students' morals. The impact of religious literacy includes changes in students' attitudes towards religion, self-confidence, humility, discipline, and responsibility. Supporting factors include the enthusiasm of teachers and students, as well as the availability of facilities, while inhibiting factors include lack of parental attention, unsupportive environments, and excessive use of gadgets.